2023
DOI: 10.3390/molecules28031337
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Roles of ISG15/ISGylation in Cancer

Abstract: The protein ISG15 encoded by interferon-stimulated gene (ISG) 15 is the first identified member of the ubiquitin-like protein family and exists in the form of monomers and conjugated complexes. Like ubiquitin, ISG15 can mediate an ubiquitin-like modification by covalently modifying other proteins, known as ISGylation. There is growing evidence showing that both the free and conjugated ISG15 are involved in multiple key cellular processes, including autophagy, exosome secretion, DNA repair, immune regulation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 97 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…In this study, the knockdown of IFI30 inhibited the proliferation, migration and invasion of breast cancer cells (33). The ISG15 protein, encoded by the ISG15 gene, is a member of the ubiquitin-like protein family and is involved in multiple key cellular processes, including autophagy, exosome secretion, DNA repair, immune regulation, and cancer occurrence and progression (34). Through in vivo and in vitro experiments, a study demonstrated that ISG15 induces CD4 T cell proliferation and invalidity and immune responses against tumors (35).…”
Section: Discussionmentioning
confidence: 81%
“…In this study, the knockdown of IFI30 inhibited the proliferation, migration and invasion of breast cancer cells (33). The ISG15 protein, encoded by the ISG15 gene, is a member of the ubiquitin-like protein family and is involved in multiple key cellular processes, including autophagy, exosome secretion, DNA repair, immune regulation, and cancer occurrence and progression (34). Through in vivo and in vitro experiments, a study demonstrated that ISG15 induces CD4 T cell proliferation and invalidity and immune responses against tumors (35).…”
Section: Discussionmentioning
confidence: 81%
“…In a systems biology analysis, we further investigated gene regulatory networks, particularly focusing on myeloid subpopulations associated with high-risk and rapid disease progression (e.g., CD14+Mono_IFN) and identified enrichment of regulatory networks for IRF2, IRF7, IRF9, and STAT1 transcription factors (TFs) ( Figure 5i-k, Supplemental Figure 14, Supplemental Table 5 ). These TFs are regulated by type I interferon (IFN-α) and promote the transcription of IFN-α stimulated genes, including ISG15 30,31 . Examining the survival association of IRF7-regulon activity within the myeloid compartment, we observed that patients with increased IRF7-regulon activity exhibited better outcomes (CoxPH P < 0.01) ( Figure 5j ).…”
Section: Resultsmentioning
confidence: 99%
“…ISG15 is a ubiquitin-like (UBL) protein stimulated upon interferon treatment and largely studied for controlling viral infection (47). Furthermore, ISG15 has also been implicated in cancers such as breast, pancreas and ovarian, where it controls various pathways including autophagy, exosome secretion, DNA replication stress response, and immune regulation (48)(49)(50)(51). Our group has previously reported alterations in interferon gamma (IFN) signaling during BE to EAC progression, which was partly influencing the GRAIL isoform switch (27).…”
Section: Discussionmentioning
confidence: 99%